(untitled) (Zdravstveni glasnik, 2024)
Social media platforms provide direct access to a vast amount of information, enabling the promotion of various content. It has become a new way of disseminating news worldwide and often influence social perception and public discourse development. Even scientists are not oblivious to the trend of using social media. Social media allows them to quickly and effectively share their research results with the global audience. Numerous studies indicate that scientists are increasingly participating in public discussions and activities on social media, with nearly half of academic researchers being a part of at least one social network. Media professionals have traditionally been the guardians of scientific information, but new media technologies grant scientists more power than ever to proactively engage in public communication. Many studies also suggest that most scientists consider media visibility important and see responding to journalists as a professional obligation, a stance endorsed by many universities and scientific organizations.